ANALISA KUALITAS DAN FORMULASI KERUPUK TEPUNG IKAN GABUS DAN BAYAM MERAH SEBAGAI SELINGAN TINGGI PROTEIN DAN ZAT BESI PADA WANITA USIA SUBUR ANEMIA - Nur Aeni, Vetty; Rosmana, Dadang; Hapsari, Agustina Indri; Hastuti, Widi; Purnawan, Asep Iwan (Jurnal Inovasi Bahan Lokal dan Pemberdayaan Masyarakat, 2022)
One of the causes of a high prevalence of WUS anemia is inadequate iron and protein intake that is less than needed. To resolve the issue, snack formulation namely crackers with high protein and iron contents snakehead fish flour, and red spinach. This snakehead fish flour has a high protein content. In snakehead fish meal the total protein content is 76.9 g/100 g. Red spinach is a vegetable high in iron content. In red spinach the Fe content is twice as large as in other vegetables, the iron content in red spinach is 7mg/100g. Both of these ingredients are used as functional food ingredients in patients with anemia because they contain high protein and iron. This study aims to determine the formulation and analyze the quality aspects of cracker products which were carried out by organoleptic tests as well as protein and iron content tests. The research design was an experimental study with a completely randomized design to get the right and proper cracker formula with a balanced formula, namely F1 (85%:15%), F2 (80%:20%), F3 (75%:25%), while to determine The level of preference and product quality was carried out through hedonic tests and for protein and iron content was carried out using Titrimetry and ICP-OES methods. Based on the results of the organoleptic test, there was a significant difference (p<0.05) in the overall organoleptic properties. However, based on the test results, it can be concluded that there is no specific difference between F2 and F3 compared to F1 on the level of color preference. Of the three formulas, F1 (85%:15%) is superior in all aspects. It is recommended that further research on the application of these crackers as an alternative distraction for anemic WUS sufferers is recommended.